De frontier até pós-frontier: regiões pioneiras no Brasil dentro do processo de transformação espaço-temporal e sócio-ecológico - Martin Coy; Michael Klingler; Gerd Kohlhepp (Confins)
If there exists a world region, where the frontier constitutes one of the large socio-temporal narratives and hence also an important field of inquiry in history, social sciences and particularly geography, then it is the Americas. This holds particularly true inasmuch as the incorporation of land through settler colonisation after Latin American countries’ independence – mainly in Argentina, Chile, Paraguay and Brazil – became one of the key instruments for opening up and developing areas, for geostrategic securing, and for economic valorisation of hinterland spaces discursively framed as free of settlements and populations. Until the mid-20th century the regional focus of Brazilian agro- frontiers had been on Southern Brazil. Afterwards, frontier regions gradually moved towards the wide peripheries of the Middle West and the Amazon region. Today it becomes clear that the founding myth of frontier “success stories” is not reproducible under the contradictory framework conditions of globalization and global change, of sustainability and regional development discourses, or between market logics and environmental governance. The three case studies analysed in this contribution represent different phases of frontier development and of the spatial shift in Brazilian frontier regions. Individual framework conditions and different development paths mark their socio-spatial development; nevertheless, connections are visible in what concerns the migration history of actors and the interregional networks that exist up to the present day. The goal of the paper is 1) to analyse the framework conditions of frontier development by applying the lifecycle approach, and 2) to assess the possibilities of identifying tipping points in regional development through an historical perspective.